Numerical study of ballast-flight caused by dropping snow/ice blocks in high-speed railways using Discontinuous Deformation Analysis (DDA). (March 2020) - Ding, Dong; Ouahsine, Abdellatif; Xiao, Weixuan; Du, Peng
Highlights: We studied the ballast flight caused by dropping Snow/Ice in high-speed railways. We analyzed the dynamic behavior of the collision between ballast and snow/ice. The velocity of the snow/ice block has a great impact on the ballast flight. The incoming angle of snow/ice influences the movement of the ballast particles. The shape of the snow/ice plays a significant role in the extent of ballast flight. Abstract: Frozen snow/ice blocks drop at high speeds from train causing the ballast to fly up and damage the car body. Thus, in this paper, we propose a numerical model based on the discontinuous deformation analysis (DDA) method to study the ballast flight caused by dropping snow/ice blocks in high-speed railways and to analyze the dynamic behavior of ballast particles during their collision with a snow/ice block. The validation of the proposed model is done by comparing the numerical results with the theoretical and the experimental ones. The numerical results show that the velocity, shape and incident angle of snow/ice block play an important role in the ballast flight. Specifically, the number and the maximum displacement of ballast particles increase as the train speed increases and the incident angle greatly affects the movement direction of ballast particles. The shape of the ice block affects the amount and extent of ballast flight.